Prevalence and intensity of Octolasmis infestation in mud crabs (Scylla spp.) in Wael coastal waters, Maluku, Indonesia - Shelly Mieke Pattipeiluhu; Endang Jamal; Bethsy Jane Pattiasina (Juvenil, 2024)
ABSTRACTOctolasmis is one of the most common barnacle species found on crabs. The prevalence and intensity of Octolasmis infestation on crabs can indicate the health of crab populations, both in nature and aquaculture systems. This study aimed to determine the prevalence and intensity of Octolasmis spp. infestation on mud crabs Scylla spp. in Wael coastal waters, Maluku, Indonesia. Seventeen mud crab samples of seven males and ten females were collected from Wael coastal waters in January-February 2024. Each crab was measured for carapace length and body weight, and the number of infested crabs and Octolasmis spp. were counted in each infested crab. Prevalence of Octolasmis spp. in mud crabs Scylla spp. reached 64.71% with intensity of 28.09 ind/crab. Female crabs had a higher prevalence, 55%, and intensity of 10,59±1,21 ind/crab than males, 45% and 7,59±0,82 ind/crab, respectively, but statistically not significantly different (P = 0.3110.05). Correlation tests showed that body weight and carapace length of mud crabs were negatively correlated with Octolasmis spp. infestation, and the relationship was weak, R = - 0.084 and - 0.133, respectively. These findings provide preliminary information on the level of Octolasmis spp. infestation in mud crabs Scylla spp. in Wael coastal waters. Comprehensive research is required using proportional sample size, including the effect of season and water quality on Octolasmis spp. infestation levels.Keywords: parasites, density, host size, crabs, barnacle